2018
DOI: 10.1097/md.0000000000008388
|View full text |Cite
|
Sign up to set email alerts
|

Associations of TCF7L2 gene polymorphisms with the risk of diabetic nephropathy

Abstract: The aim of the study was to explore the correlation between rs7903146 and rs290487 polymorphisms in transcription factor 7-like 2 (TCF7L2) gene and diabetic nephropathy (DN) in Chinese Han population.Polymerase chain reaction–restriction fragment length polymorphism was used to determine genotypes of TCF7L2 polymorphisms in 90 patients with DN and 96 diabetes patients without DN. The linkage disequilibrium (LD) and haplotype analysis were performed with haploview software. Hardy–Weinberg equilibrium was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Finally, considering recent emerging evidences regarding the correlation between ZIKV and diabetes mellitus, our approach explains how the reduction of some TFs can be associated to pancreatic agenesis and/or disturbing its normal function. In particular PDX1 (Pancreas/Duodenum Homeobox Protein 1; OMIM 600733) is associated with early-onset of insulin dependent diabetes mellitus [ 45 ]; NKX6-1 (NK6, Homolog of Drosophila 1O; OMIM 602563) is implicated in development of insulin producing beta cells in the islets of Langerhans [ 46 ]; and TCF7L2 (Transcription Factor 7-Like 2; OMIM 602228) is involved in blood glucose homeostasis [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, considering recent emerging evidences regarding the correlation between ZIKV and diabetes mellitus, our approach explains how the reduction of some TFs can be associated to pancreatic agenesis and/or disturbing its normal function. In particular PDX1 (Pancreas/Duodenum Homeobox Protein 1; OMIM 600733) is associated with early-onset of insulin dependent diabetes mellitus [ 45 ]; NKX6-1 (NK6, Homolog of Drosophila 1O; OMIM 602563) is implicated in development of insulin producing beta cells in the islets of Langerhans [ 46 ]; and TCF7L2 (Transcription Factor 7-Like 2; OMIM 602228) is involved in blood glucose homeostasis [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…(Pancreas/Duodenum Homeobox Protein 1; OMIM 600733) is associated with earlyonset of insulin dependent diabetes mellitus [45], NKX6-1 (NK6, Homolog of Drosophila 1O; OMIM 602563) is implicated in development of insulin producing beta cells in the islets of Langerhans [46] and TCF7L2 (Transcription Factor 7-Like 2; OMIM 602228) is involved in blood glucose homeostasis [47].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, two studies conducted by Buraczynska et al [ 17 , 22 ] has verified that the rs7903146-T allele of TCF7L2 gene was significantly associated with DN, especially in the early stage of diabetes. Zhuang et al [ 18 ] carried out a case-control study in Chinese population, and found that TCF7L2 rs7903146 polymorphism had a significant impact on the susceptibility to DN in Chinese Han population, but rs290487 had no statistical association with DN. This was consistent with conclusions from Lewis et al [ 23 ], Hussain et al [ 12 ] and Sale et al [ 24 ], But Fu et al [ 25 ] concluded inconsistent results on relationship between TCF7L2 rs7903146 polymorphism and DN risk, in this study, just 248 DN patients were included in the analysis, so the limited sample size maybe the reason for inconsistent results between this study and our study.…”
Section: Discussionmentioning
confidence: 99%